High-responsivity plasmonics-based GaAs metal-semiconductor-metal photodetectors - Karar, A.; Das, Narottam; Tan, C.; Alameh, K.; Lee, Y.; Karouta, F. (American Institute of Physics, 2011)
We report the experimental characterization of high-responsivity plasmonics-based GaAsmetal-semiconductor-metalphotodetector (MSM-PD) employing metal nano-gratings. Both the geometry and light absorption near the designed wavelength are theoretically and experimentally investigated. The measured photocurrent enhancement is 4-times in comparison with a conventional single-slit MSM-PD. We observe reduction in the responsivity as the bias voltage increases and the input light polarization varies. Our experimental results demonstrate the feasibility of developing a high-responsivity, low bias-voltage high-speed MSM-PD.